Penambahbaikan Pengurusan Keselamatan Terhadap Buruh Mahir di Tapak Bina - Ahmad Hilmi, Nur Syahirah; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2025)
The construction industry is a primary catalyst that significantly contributes to the national economy. Skilled workers play a crucial role on construction sites, ensuring high-quality workmanship, efficiency, and safety compliance, as they possess specialized knowledge and skills to complete complex tasks. Nevertheless, managing the safety of skilled workers on construction sites is one of the issues that frequently arise in the construction industry. This study was carried out to identify the factors that cause problems in the safety management of skilled workers at the construction site, identify the challenges faced by the management in overcoming the problem of safety management of skilled workers at the construction site, and suggest improvements in the safety management of skilled workers at the site. This quantitative study focused on G7 Contractors at Johor Bahru, Johor. The research findings were obtained from a total of 125 respondents through the distribution of questionnaire forms. To facilitate data processing, Statistical Package of the Social Sciences (SPSS) version 26 was used. The results of the data analysis show that skilled workers not complying with the contractor's instructions related to safe work procedures are the main factor contributing to the problem of safety management at the construction site. The challenge faced by management in overcoming the problem of safety management for skilled workers at the construction site is that it requires the cost of providing sensors and cameras for safety monitoring. A suggestion to improve the challenge is to use CCTV to monitor the safety of the workers at the construction site. In conclusion, this study can help contractors prepare more effectively and develop thorough plans to address labor or worker management issues at construction sites, particularly for skilled workers.